(untitled) (Acta Polytechnica CTU Proceedings, 2022)
A small set of query variables designed to collect information about the energy-related features of residential buildings is presented. These “energy profile indicators” include information about those visible characteristics of a building which have a notable impact on its energy performance and are simple to assess. The queries are an interesting source for a rough energy performance calculation for single buildings as well as for housing portfolios or housing stocks. A method has been developed to transform the energy profile indicators into input data for a physical calculation model. It consists of procedures to estimate the envelope area, U-values, and efficiency values of the heat supply system. To all model input variables an uncertainty is assigned. If information from a query is not available, the model input is set to a state representing the average building stock and the uncertainty of this quantity is adjusted to a value reflecting the variance in the stock. The resulting uncertainty of the calculated energy use is determined. Examples of the application of the method are given to show the influence of different unknown quantities including occupant behaviour. Experiences on the coherence with metered consumption are reported.